A Cost Effective Weather Monitoring Device - K. E. Ukhurebor; I. C. Abiodun; S. O. Azi; I. Otete; L. E. Obogai (Archives of Current Research International, 2017)
Getting the latest weather parameters and taking the necessary precautions about the recent climate induced environmental disasters have become a major course of concern in this era of global warming. In this research a cost effective weather monitoring device was constructed using an Arduino Mega 2560 microcontroller and some contemporary suitable sensors with a real time data logger and LCD. The constructed weather monitoring system is beneficial in terms of its on-device display, smaller size, cost effective, flexibility and portability as well simplicity in its operation and would be used for some meteorological measurements. The data acquired from this constructed device were in good conformity with those obtained from other sources and would make weather data readily available for small-scale users like farmers, travellers, aircraft workers, researchers, institutions and others for the purpose of measuring, monitoring, analyzing and prognosticating of the climate in other to minimize climate-induced disasters in our environment.